Molecular modeling of the piezoelectric effect in the ferroelectric polymer poly(vinylidene fluoride) (PVDF) - Bystrov, Vladimir S.
In this work, computational molecular modeling and exploration was applied to study the nature of the negative piezoelectric effect in the ferroelectric polymer polyvinylidene fluoride (PVDF), and the results confirmed by actual nanoscale measurements. First principle calculations were employed, using various quantum-chemical methods (QM), including semi-empirical (PM3) and various density functional theory (DFT) approaches, and in addition combined with molecular mechanics (MM) methods in complex joint approaches (QM/MM). Both PVDF molecular chains and a unit cell of crystalline beta-phase PVDF were modeled. This computational molecular exploration clearly shows that the nature of the so-called negative piezo-electric effect in the ferroelectric PVDF polymer has a self-consistent quantum nature, and is related to the redistribution of the electron molecular orbitals (wave functions), leading to the shifting of atomic nuclei and reorganization of all total charges to the new, energetically optimal positions, under an applied electrical field. Molecular modeling and first principles calculations show that the piezoelectric coefficient d (33) has a negative sign, and its average values lies in the range of d (33) similar to -16.6 to -19.2 pC/N (or pm/V) (for dielectric permittivity epsilon = 5) and in the range of d (33) similar to -33.5 to -38.5 pC/N (or pm/V) (for epsilon = 10), corresponding to known data, and allowing us to explain the reasons for the negative sign of the piezo-response. We found that when a field is applied perpendicular to the PVDF chain length, as polarization increases the chain also stretches, increasing its length and reducing its height. For computed value of epsilon similar to 5 we obtained a value of d(31) similar to +15.5 pC/N with a positive sign. This computational study is corroborated by measured nanoscale data obtained by atomic force and piezo-response force microscopy (AFM/PFM). This study could be useful as a basis for further insights into other organic and molecular ferroelectrics.